Optimizing Weld Bead Geometry for High-Performance ‎Welding of Stainless-Steel Using Grey Relational Analysis - C, Dr. Sivakumar; R., Dr. Balusamy; M., Mr. Surendran; Kumar, Mr. Naveen; M., Mr. MohideenBatcha; P.L., Mr. Srenatthan (International Journal of Basic and Applied Sciences, 2025)
This study focuses on optimizing the weld bead geometry in Metal Inert Gas (MIG) butt-welding of stainless steel using Grey Relational ‎Analysis (GRA). Process parameters significantly influence weld quality, and suboptimal conditions often result in joint failure. Traditional ‎trial-and-error approaches have been replaced by advanced computational and statistical techniques to enhance process efficiency and ‎reliability. This research investigates the relationship between welding parameters—such as welding current, welding speed, and arc ‎voltage—and key output responses, including bead penetration, tensile strength, and microhardness. GRA, which efficiently ranks ‎parameter combinations according to a gray relational grade, was used to build a multi-objective optimization technique. Analysis of variance ‎‎(ANOVA) was used to determine the importance of each factor, and confirmation tests were performed to verify the optimal settings. The ‎results demonstrate improved weld quality and mechanical properties, confirming the effectiveness of the proposed methodology in ‎optimizing stainless steel welding‎.